Reaction induced multifunctional TiO2 rod/particle nanostructured materials for screen printed dye sensitized solar cells. Issue 6 (15th March 2021) - Selvapriya, R.; Sasirekha, V.; Vajeeston, P.; Pearce, J.M.; Mayandi, J.
Abstract: This study investigates the potential of utilizing multifunctional nanostructured materials for the efficient light trapping and electron transport in solar cells by combining titanium dioxide (TiO2 ) rods and nanoparticles. A simple solvothermal method was adopted for the synthesis of coupled morphology adopting the desired precursor with the constant concentration and temperature. The reaction duration (12, 24, 36 and 48 h) was varied and the materials resultant physical, optical and structural characteristics were elucidated to determine the nature of the prepared material. The crystallographic phase of the synthesized samples was determined with XRD and Raman analysis. From the experimental data it is hypothesized that the surface plane of anatase (105) is involved in the deformation of the structure and the formation of the rutile phase. To further investigate on the formation of mixed phase in the prepared sample a computation study was performed using density functional theory coupled to the Hubbard U correction (DFT + U) as a function of volume in both the anatase and rutile phases. The relative stability of the O–Ti–O networks is explored starting from ultrathin materials for four different sizes, of anatase and rutile nanorods separately. Finally, the synthesized TiO2 materials were used to prepare screen printed dye sensitized solar cell (DSSC) devices and their respective properties were quantified.